Stud and wire arc additive manufacturing—Development of a combined process for the high-productivity additive manufacturing of large-scale lattice structures - F. Riegger; D.L. Wenzler; M.F. Zaeh (Journal of Advanced Joining Processes, 2024)
Metallic large-scale freeform lattice structures can be manufactured by wire arc additive manufacturing (WAAM). These structures are especially interesting for applications in civil engineering, such as lightweight structural elements and reinforcement structures. One promising approach for the efficient additive manufacturing of lattice structures is extending WAAM through drawn-arc stud welding (DASW). In this innovative combined process, called stud and wire arc additive manufacturing (SWAAM), WAAM is used for producing geometrically complex lattice segments (e.g., nodes) and DASW for straight segments. This paper presents the proof of concept showing the feasibility of this novel approach with a robotic test setup. Specimens consisting of bars with a diameter of 8 mm were produced with WAAM and SWAAM. The temperature development in the samples during manufacturing and their production time were measured. WAAM resulted for the first layer in a maximum temperature of 343 °C at a distance of 10 mm to the weld zone, while SWAAM showed 213 °C. The production time of a given test geometry was reduced by 57.7 % for the hybrid process compared to a pure WAAM manufacturing. This proves that reducing the welding operations by using studs decreases the heat input, lowers the process temperatures, and increases the production rate.